Comparison Of Isoconazole Nitrate Versus Nystatin For The Treatment Of Otomycosis - Kausar, Amna; Chaudhry, Sadia; Qammar, Nighat; Akram, Ansa Umara; Alamgir, Ashar; Hussain, Wajid (Journal of Rawalpindi Medical College, 2023)
Objective: To compare the efficacy and local adverse effects of Isoconazole Nitrate versus Nystatin for the treatment of patients having Otomycosis Sudy Design: Group experimental study. Study Setting & Duration: Department of Otolaryngology, Head & Neck Surgery at Rawalpindi Teaching Hospital, Rawalpindi. Duration of study was 6 months after approval by Ethical Committee from Feb 2023 to july 2023 Materials and Methods: Total of 64 patients were selected. The study participants were individuals who, according to operational definitions had Otomycosis and who had presented for evaluation at the Department of Otolaryngology Rawalpindi teaching Hospital, Rawalpindi. They also met all inclusion and exclusion criteria requirements and these requirements were strictly adhered to in order to control confounders and bias. Isoconazole nitrate ointment was used to treat patients in Group A and Nystatin ointment was used to treat instances in Group B. Patients were chosen by randomization using lottery method. SPSS 28 was used to determine the frequencies in the data. Results: 64 individuals (32 cases in each group) were chosen for the study by the ENT outpatient clinic. Out of which 33 (51.6%) being female and 31 (48.1) being male. The age ranged from 12 to 80 years, with a mean age of 44.29 ±19.13. After two weeks, there was a substantial improvement in 25 (39.06%) of the group A patients (p=0.08), a moderate improvement in 7 (10.9%), and a minor improvement in 5 (7.81%) patients (p=0.37) while in group B exhibited a substantial improvement in just 19 (10.9%) (p=0.08), a moderate improvement in 9 (39.0%) (p=0.38), and a small improvement in 7 (42.19%) (p=0.37). After four weeks 21 (32.81%) in Group B showed insignificant improvement, while 26 (40.63%) in Group A exhibited better improvement than Group B. The treatment for group A, which included isoconazole nitrate, was substantially more successful than the Nystatin treatment for group B. Isoconazole was found insignificantly more effective than (p=0.08). The majority of patients in both groups didn’t notice any adverse . Conclusion: Nystatin was shown to be significantly less efficacious than isoconazole nitrate ointment in treating otomycosis.